Die wetenskapsleer van V. Hepp - Kock, Pieter de Bruyn (University of the Free State, 1954)
Abstract not available
Dissertation (M.A. (Philosophy))--University of the Free State, 1954
Keywords: Knowledge, Theory of; Hepp, V. -- (Valentine), -- 1879-1950